Letters to a Prisoner - JACQUES GOLDSTYN (Toronto, Canada Owlkids, 2017)
Told entirely through illustrations, Letters to a Prisoner is a wordless story about the power of hope and the written word. Inspired by Amnesty International's letter-writing campaigns to help free people who have been jailed for expressing their opinion, the book tells the story of a man who is arrested during a peaceful protest. In solitary confinement, he begins to despair--until a bird delivers a letter of support written by somebody outside the prison. Every day more missives arrive until the prisoner escapes his fate on wings made of letters. Simple illustrations convey plenty of rich symbolism to provoke thought and discussion. A letter from the author provides more information about Amnesty International's Write for Rights campaign.
Keywords: Circle Time Book - Equality & Justice; Wordless Books -- Wordless Books